Adaptive coping strategies of behavior as a condition for preserving and maintaining the psycho-emotional health of teachers - Мощенко, Марина; Попова, Ольга (SWorldJournal, 2020)
Psychoemotional health of a teacher is a factor of success of the educational system and determines the effectiveness of the process of education and training of preschool children, especially during the period of education reform. The study of stress re